PENGEMBANGAN MEDIA PEMBELAJARAN IPAS BERBANTUAN NEARPOD PADA “MATERI NORMA DAN ADAT ISTIADAT DI DAERAHKU” DI SEKOLAH DASAR - Apriliani, Diah; Asnawi; Aprilia, Rapita (STKIP Subang, 2026)
This research was conducted with the following objectives: (1) to identify the development of Nearpod-assisted learning media on the topic “Norms and Local Customs in My Region” in elementary schools; (2) to determine the validity of the Nearpod-assisted learning media on the topic “Norms and Local Customs in My Region” in elementary schools; and (3) to determine the practicality of the Nearpod-assisted learning media on the topic “Norms and Local Customs in My Region” in elementary schools.This study is a research and development (R&D) study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were fourth-grade students and teachers at SD Negeri 9 Kuala Langsa, as well as material experts, media experts, and language experts.The results of the validation tests showed that the material expert validation obtained a percentage of 93.33% (very valid category), media expert validation obtained 95% (very valid category), and language expert validation obtained 100% (very valid category). These results indicate that the Nearpod-assisted learning media is very valid and can be implemented in schools. Based on the implementation results, the teacher’s response reached 93% (very practical category), and the students’ response reached 94.64% (very practical category).